Relationships Between Environmental Factors and the Quality of Berries Grown in the Fort McMurray Region, Alberta - De Silva, Chathumi (Université d'Ottawa / University of Ottawa, 2023)
Fort McMurray has experienced significant environmental disruptions, raising concerns about chemical releases that affect the environment, particularly berries. This thesis explores the relationship between environmental factors and the nutritional quality of pin cherry (Prunus pensylvanica L.F.) and common blueberry (Vaccinium myrtilloides Michx) fruits and soil in Fort McMurray (reclaimed and natural lands). Samples were collected in August 2022 and analyzed for chemicals and quality variables. The results revealed concentration variations among samples, with hydrocarbons higher in reclaimed areas and blueberries than others and soil surpassing those in fruits. Copper and iron in fruits exceeded regulatory limits. A strong association between soil chemicals and alkylated hydrocarbons in fruits explained most differences. Soil trace elements and properties were primary environmental drivers, while hydrocarbons were secondary influencers, evident mainly in reclaimed berry environments. Antioxidant-focused nutritional quality in reclaimed berries was predominantly influenced by these key drivers in soil, requiring consistent monitoring.
Keywords: Environmental factors; nutritional quality; Health metrics; Antioxidants; Trace Elements; Polycyclic aromatic hydrocarbons; Physicochemical properties; Oil Sands Reclamation; Berries; Fort McMurray; Alberta